WACANA ESTETIKA ISLAM DALAM SASTERA KANAK-KANAK INDONESIA ERA ORDE BARU TAHUN 1980-AN: ISLAMIC AESTHETIC DISCOURSE IN INDONESIAN CHILDREN’S LITERATURE IN THE ERA OF THE 1980’S NEW ORDER - Susanto, Dwi; Prasojo, Albertus; Wati, Rianna; ., Murtini (Jurnal Pengajian Melayu (JOMAS), 2021)
Abstract This research focused on the spread of aesthetic discourse in Islamic literature, especially Islamic Indonesian children’s literature which was marginalised in Indonesian literature history. The paper aimed to identify the system of exclusion or prohibition, restrictions to discourse and genealogical aesthetics of Islamic children’s literature. The data utilised were various discourses available in Indonesian literature, aesthetics in the history of the literature mentioned, Indonesian literary experts and critics’ opinions, and different information related to the topic. Data interpretation was executed based on the strategy introduced by Michel Foucault on discourse and power. Results showed that the discourse of Islamic literary aesthetics was deliberately eliminated during the New Order era because it was believed to be a part of the right-wing political power apparatus. That exclusion was carried out with restrictions and prohibitions by highlighting the aesthetics of development and modernity as the dominant aesthetic discourse in Indonesian literature, such as universal humanism. The history of aesthetic discourse in Islamic literature, including Islamic children’s literature, appeared significantly during the Post-Reformation era due to the New Order’s collapse. Hence aesthetic discourses that emerged afterwards were highly diverse and on par with other genres. Keywords: Islamic literary aesthetic discourse, children’s literature, Indonesian literary history.